Differences and Similarities of Acid-Extracted Lignin versus DES-Extracted Lignin - Ioana Popa-Tudor; Victor Alexandru Faraon; Diana Constantinescu-Aruxandei; Florin Oancea (Proceedings)
In recent decades, the circular bioeconomy has been of major global interest [...]